Forming ferrocenyl self‐assembled monolayers on Si(100) electrodes with different alkyl chain lengths for electron transfer studies - A. Ahmad, Shahrul A.; Ciampi, Simone; Parker, Stephen G.; Gonçales, Vinicius R.; Gooding, J. Justin (Wiley, 2019)
The reaction of hydrogen-terminated Si(100) with 1,8-nonadiyne was previously shown to afford robust surfaces where oxidation of the substrate is not evident. Here, the experimental conditions required for reacting hydrogen-terminated Si(100) with α,ω-diynes of different lengths is explored via thermal hydrosilylation of 1,6-heptadiyne, 1,8-nonadiyne, 1,10-undecadiyne and 1,15-hexadecadiyne. X-ray photoelectron spectroscopy indicated monolayers were successfully formed with oxide levels below the XPS detection limit for molecules with lengths varying from 7 to 11 carbons. It was observed that the apparent rate of electron transfer (ket) was affected not only by the SAM thickness, but also by hopping between ferrocene moieties where the presence of tiny oxidative defects act as electron transfer hotspots.